Microanatomical considerations for safe uncinate removal during anterior cervical discectomy and fusion: 10‐year experience. Issue 6 (13th April 2020) - Clifton, William; Valero‐Moreno, Fidel; Vlasak, Alexander; Damon, Aaron; Tubbs, R. Shane; Merrill, Sarah; Pichelmann, Mark
Abstract: Cervical radiculopathy from uncovertebral joint (UVJ) hypertrophy and nerve root compression often occurs anterior and lateral within the cervical intervertebral foramen, presenting a challenge for complete decompression through anterior cervical approaches owing to the intimate association with the vertebral artery and associated venous plexus. Complete uncinatectomy during anterior cervical discectomy and fusion (ACDF) is a controversial topic, many surgeons relying on indirect nerve root decompression from restoration of disc space height. However, in cases of severe UVJ hypertrophy, indirect decompression does not adequately address the underlying pathophysiology of anterolateral foraminal stenosis. Previous reports in the literature have described techniques involving extensive dissection of the cervical transverse process and lateral uncinate process (UP) in order to identify the vertebral artery for safe removal of the UP. Recent anatomical investigations have detailed the microanatomical organization of the fibroligamentous complex surrounding the UP and neurovascular structures. The use of the natural planes formed from the encapsulation of these connective tissue layers provides a safe passage for lateral UP dissection during anterior cervical approaches. This can be performed from within the disc space during ACDF to avoid extensive lateral dissection. In this article, we present our 10‐year experience using an anatomy‐based microsurgical technique for safe and complete removal of the UP during ACDF for cervical radiculopathy caused by UVJ hypertrophy.